2021
DOI: 10.1002/14651858.cd007899.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Paying for performance to improve the delivery of health interventions in low- and middle-income countries

Abstract: Background There is growing interest in paying for performance (P4P) as a means to align the incentives of healthcare providers with public health goals. Rigorous evidence on the effectiveness of these strategies in improving health care and health in low‐ and middle‐income countries (LMICs) is lacking; this is an update of the 2012 review on this topic. Objectives To assess the effects of paying for performance on the provision of health care and health outcomes in low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 158 publications
4
75
1
Order By: Relevance
“…The framework’s complexity and its interdependencies reinforce that there is no ‘one-size-fits-all’ blueprint for performance management. 51 Interventions must be carefully calibrated to the context of the health system, the culture of its organisations, and the motivations of its individuals. Failing to engage with context can contribute to well-meaning interventions not having their anticipated effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The framework’s complexity and its interdependencies reinforce that there is no ‘one-size-fits-all’ blueprint for performance management. 51 Interventions must be carefully calibrated to the context of the health system, the culture of its organisations, and the motivations of its individuals. Failing to engage with context can contribute to well-meaning interventions not having their anticipated effects.…”
Section: Discussionmentioning
confidence: 99%
“…50 The literature shows the challenges of designing an approach that effectively promotes performance without unintended consequences. 51 System-level enabling environment Performance management requires organisations to have the opportunity to perform, with sufficient agency over outcomes. 52 This requires adequate hardware resources (eg, infrastructure, supplies and human resources).…”
Section: System-level Performance Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In low-and middle-income countries these interventions are typically implemented at the facility level but they can be directly targeted to individual health workers. 8 , 9 Measurable targets may include health outcomes, delivery of interventions, utilization of services and quality of care. 8 , 9 While many published reviews highlight incentives as an important element of CHW programmes, we found no specific evidence on the impact of performance-based incentive interventions on measurable outcomes of CHWs’ performance.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies mainly analyzed the relationship between proportion of performance-based income and the behaviors of health workers, and have varied ndings under different settings, and several systematic reviews have con rmed that it was hard to get conclusion on it because the heterogeneity in speci c payment design and contexts [14,15]. Some studies concluded that low proportion of income being linked to performance was not enough to motivate the behavior of health workers and improve the performance [16,17], and little gap in income levels of health workers with difference performance could not incentivate the performance improvement [18].…”
Section: Discussionmentioning
confidence: 99%